Optimalisasi Hilirisasi Bisnis Maggot Melalui Peningkatan Sarana Dan Prasarana, Tata Kelola Dan Strategi Pemasaran Berbasis Digital Pada Bank Sampah Unit Siliwangi Bogor - Nurendah, Yulia; Sutarti, Sutarti; Munawar, Aang; Mulyana, Mumuh; Nurachmad, Edi; Setiawan, Budi; Maulina, Dwi; Lestari, Febriana Indah (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The aim of the Partnership-Based MSME Development activity is to resolve the problems of the Siliwangi Waste Bank Unit (BSU) as a collaboration partner. The problems faced by related partners are organizational management, resources and marketing. From an administrative point of view problems arise, for example. there are no guidelines regarding the functions and duties of organizational management, weak administrative management and financial reporting systems. In terms of resources, the problem is that BSU Siliwangi administrators are still weak in understanding organizational development, entrepreneurship and marketing strategies, Magot cultivation skills that need to be improved. The marketing problem is that BSU Siliwangi's marketing strategy has not optimally used digital technology. Based on these problems, several community partnership program activities were implemented, such as training in the use of management and information systems in partner organizations, entrepreneurship training and the use of technology in company development. Training related to organizational management consists of financial management and administration, entrepreneurship training, marketing strategies using digital technology, and Magot cultivation training. The results of this activity are: 1) Establishment of partner organization governance guidelines as well as a simple financial management and recording system for partner organizations; 2) Availability of adequate production facilities, especially vital facilities such as waste chopping machines for Magot feed; 3) Increasing understanding of management and members regarding asset management, capital, entrepreneurship and digital-based marketing strategies through soft skills training and mentoring programs; 4) Establishment of a digital marketing platform in the form of the Web and other digital features (social media Instagram and Tiktok); 5) Increased income at partner organizations; 6) Publication of the results of community partnership program activities in the form of articles in print media and activity videos; 7) Have a Business Identification Number (NIB). Keywords: governance, marketing strategy, downstreaming, digital business, waste bank